Effect of the Substitution Pattern on the Intramolecular Charge‐Transfer Emissions in Organoboron‐Based Biphenyls, Diphenylacetylenes, and Stilbenes. Issue 12 (10th September 2013) - Yan, Yi‐Qiao; Li, Yan‐Bang; Wang, Jian‐Wu; Zhao, Cui‐Hua
Abstract Three series of organoboron‐based molecules, including biphenyls 1a, 1b, 1c, diphenylacetylenes 2a, 2b, 2c, and stilbenes 3a, 3b, 3c, in which the electron‐accepting boryl and the electron‐donating amino groups are introduced at different positions, have been comprehensively investigated to explore the effect of the substitution pattern on the intramolecular charge‐transfer emissions. In cyclohexane solution, the change of substitution pattern from p, p′ to o, p′ by introduction of boryl at the lateral o‐position rather than the terminal p‐position leads to bathochromism in the absorption and emission spectra. With further variation of the amino position from the terminal p′‐position in o, p′‐substitution to the lateral o′‐position in an o, o′‐substitution pattern, a blueshift was observed in the absorption owing to the less‐efficient conjugation extension of the amino group as the result of sp3 hybridization. It is notable that the emission of the three series of molecules changes with completely different trends. Only the emission of the biphenyl is redshifted further from o, p′‐substituted 1b to o, o′‐substituted 1a, whereas o, o′‐substituted diphenylacetylene 2a maintains almost the same spectrum as that of o, p′‐substituted diphenylacetylene 2b and the fluorescence of o, o′‐substituted stilbene 3a is even blueshifted compared with o, p′‐substituted stilbene 3b. As a result, the o, o′‐substituted biphenyl 1a shows the longest emission wavelength despite the limited conjugation of the parent biphenyl skeleton. The long emission wavelength of 1a may arise from its extremely twisted structure, which would cause a significant structural relaxation in the exited state. In the solid state, 1a still keeps almost the longest emission wavelength. In addition, its quantum yield is also among the highest. The unusual properties, intense solid‐state emission together with long emission wavelength, and particularly large Stokes shift, which are difficult to attain by structural modification of other parent π‐conjugated frameworks, have been achieved by the introduction of boryl and amino groups at the o, o′‐positions of the biphenyl skeleton.